2009
DOI: 10.1089/thy.2009.1609
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from Mouse Models of Thyroid Cancer

Abstract: Background: Thyroid cancer is the most common endocrine tumor and is increasing in incidence. The aim of this study was to review mouse models of differentiated thyroid cancer and how they elucidate human thyroid cancer biology. Summary: Differentiated thyroid cancer, primarily papillary and follicular, comprises the majority of thyroid cancers. There has been tremendous growth in the cross-talk between basic science and clinical practice for thyroid cancer management. Insight into the framework of genes respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 96 publications
2
52
0
3
Order By: Relevance
“…In addition, the targeted expression of BRAF-V600E in thyroid cells of transgenic mice results in development of invasive PTC with poorly www.intechopen.com differentiated foci that closely recapitulate the phenotype of BRAF-positive PTC in humans. The BRAF-V600E mice had a 30% decrease in survival at 5 months (Kim and Zhu, 2009 and references therein). Fig.…”
Section: The Serine/threonine Kinase Brafmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the targeted expression of BRAF-V600E in thyroid cells of transgenic mice results in development of invasive PTC with poorly www.intechopen.com differentiated foci that closely recapitulate the phenotype of BRAF-positive PTC in humans. The BRAF-V600E mice had a 30% decrease in survival at 5 months (Kim and Zhu, 2009 and references therein). Fig.…”
Section: The Serine/threonine Kinase Brafmentioning
confidence: 99%
“…knockout of the tumor-suppressor p53) to result in metastasis (Kim and Zhu, 2009 and references therein). By contrast, RET/PTC3 mice develop PTC-like lesions that are similar to the human solid variant of PTC, and unlike RET-PTC1 mice, in about one-third of cases, develop axillary lymph node metastasis (Kim and Zhu, 2009 and references therein). Although transgenic mouse models have shown that RET/PTC rearrangements can initiate thyroid carcinogenesis in vitro, the same studies have indicated that RET/PTC represents a weak tumour-initiating event, requiring additional genetic and/or epigenetic changes for clonal expansion of mutated cells.…”
Section: Tyrosine Kinase Receptorsmentioning
confidence: 99%
See 3 more Smart Citations